An integrated rock magnetic and EPR study in soil samples from a hydrocarbon prospective area - Gonzalez-Lucena, Fedora; Aldana, Milagrosa; Costanzo-Alvarez, V.; Diaz, M.; Romero, I. (My University, 2002)
Magnetic susceptibility (MS) and organic matter free radical concentration (OMFRC) determined by electron paramagnetic resonance, have been measured in soil samples ( nearly equal 1.5 m depth) from an oil prospective area located at the southern flank of the Venezuelan Andean Range. S-ratios close to 1, as well as high temperature susceptibility analyses, reveal magnetite as the chief magnetic phase in most of these samples. Ethane concentrations, MS and OMFRC normalized data have been plotted against the relative position of 22 sampling sites sequentially arranged from north to south. Although there is not a linear correlation between MS and OMFRC data, these two profiles seem to vary in like fashion. A MS and OMFRC southern anomaly coincides with the zone of highest ethane concentration that overlies a "Cretaceous kitchen". OMFRC highs could be linked to the degradation or alteration of organic matter, the possible result of hydrocarbon gas leakage, whose surface expression is the stressed fern observed by remote sensing studies previously performed in the area. Ethane anomalies are associated to this seepage that also produces changes in the magnetic mineralogies detected as MS positive anomalies.
Keywords: magnetic susceptibility; organic matter free radical concentration; OMFRC; electron paramagnetic resonance; Venezuelan Andean Range; ethane concentration; ethane anomalies; seepage; magnetic mineralogies